Lives Saved or Lives Lost? The Effects of Concealed Handgun Laws on Crime - Dezhbakhsh, Hashem; Rubin, Paul H. (American Economic Review, 1998)
Lives Saved or Lives Lost? The Effects of Concealed-Handgun Laws on Crime Author(s): Hashem Dezhbakhsh and Paul H. Rubin Source: The American Economic Review, Vol. 88, No. 2, Papers and Proceedings of the Hundred and Tenth Annual Meeting of the American Economic Association (May, 1998), pp. 468-474 Published by: American Economic Association Stable URL: http://www.jstor.org/stable/116969 Accessed: 05/09/2008 17:45